Pathways towards green management policies in public sector / Nur'ain Achim, Nur Hairani Abd Rahman and Nur Liyana Mohd Kamil - Achim, Nur'ain; Abd Rahman, Nur Hairani; Mohd Kamil, Nur Liyana (Universiti Teknologi MARA (UiTM), 2022)
Sustainable development is becoming the topic most discussed nowadays. It is a universal issue targeting peace and freedom for people, the planet and prosperity. Supporting sustainable sectors, encouraging sustainable lifestyles, and allocating time and resources to scientific research are important strategies to promote sustainable development. This research paper purposes a theoretical framework of green HRM and its effects on an organization's sustainable performance. This study aims to understand the influence of green human resource management (green HRM) practices on sustainable performance in Malaysia's public service organizations. This article is expected to help researchers develop an interest in green HRM and perhaps gain conceptual knowledge of this as well. Finally, this paper is expected to provide a deeper understanding of the managerial perspectives on green HRM and the perceived importance of sustainable performance for future researchers.